Towards photovoltaic module waste management in the Philippines review of strategies and regulatory framework - Diccion, Antonio L. Jr.; Duran, Jeffrey Z. (2023)
Accessible online through this link: https://journals.upd.edu.ph/index.php/pej/article/view/9140/8068
Keywords: Photovoltaic power systems; Waste management; Sustainable development